y =2x-3 2x – 2y = 2 How do I solve this

Question

y =2x-3
2x – 2y = 2

How do I solve this

in progress 0
Yến Oanh 1 year 2021-09-01T09:34:37+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-01T09:36:00+00:00

    Answer:  ans= y=1 (please look at the step by step explanation)

    Step-by-step explanation: 2x-2y=2

    2x-(2x-3)=2

    2x-2x+3=2

    2x-2+3=2

    0+3=2

    therefore, y=2x-3

    2x-2y=2

    2x-2(2x-3)=2

    2x-4x+6=2

    -2x+6=2

    -2x=6

    -2x-2y

    therefore x=y/-2= -2/

    y=2x-3

    y=2 multiplied by 2 -3

    y=y-3

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )